Meningkatkan Hasil Belajar Siswa Muatan Ppkn Menggunakan Model Be Smart Pada Kelas VA SDN Telawang 3 Banjarmasin - Erika Fitriana; Ari Hidayat (CV. ITTC INDONESIA, 2024)
The research problem is students learning outcome. This is because students have difficulty understanding PPKn material in learning, both in terms of concepts and problem solving. Students who still have difficulty in PPKn content will have an impact on their cognitive aspects. In the cognitive aspect, the knowledge transfer process which still takes place in one direction is a conventional method which results in students being passive during the learning process so that they are not able to explore the material in more depth, understand concepts, making it difficult to analyze problem solving. Efforts to overcome this problem are by apply the BE SMART model in learning. Determining the learning outcomes for students is the goal of this study.This research used Classroom Action Research (PTK) which was carried out in 4 meetings in VA clas of SDN Telawang 3 Banjarmasin with a total of 22 students. Both qualitative and quantitative methods are used in this study. The dataa taken is qualitative data obtained through observation and then uses quantitative data for student learning outcomes obtained through group and individual written tests. Based on the results of this research, it can be concluded that using the BE SMART model can improve student learning outcomes. The results of research using the BE SMART model show that learning outcomes in the cognitive aspect increased from 45% to 100%, the affective aspect increased from 45% to 100% and finally the psychomotor aspect from 32% to 100%. In light of the findings of this study, it can be concluded that using the BE SMART model can enhance the educational results of students.